Pembuatan Alat Ukur Kualitas Air Berbasis Arduino untuk Peningkatan Kompetensi Teknologi Siswa SMK - Tunjung Genarsih; Angga Dwinanda; Ardianto Syaifur Rohman; Sihmaulana Dwianto; Prisilia Angel Tantri (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2026)
SMK Darul Hikmah faces challenges in enhancing students' technological competencies, particularly in applied technology and environmental problem-solving. This community service activity aims to improve students' technical skills through a Workshop